Material handling and registration for an additive manufacturing-based hybrid system. (October 2017) - Ambriz, Steven; Coronel, Jose; Zinniel, Bob; Schloesser, Ron; Kim, Chiyen; Perez, Mireya; Espalin, David; Wicker, Ryan B.
Highlights: A Multi3D System, which provides both, additive and subtractive machines working in synchronicity, was developed. This system allows for the fabrication of multi-functional end use parts including those with multiple materials and embedded electronics. A hybrid manufacturing system consisting of a material handling robot, a portable build platform, a heated travel envelope, and an end effector, was developed. This system provides full automation in the transfer of a workpiece between the various manufacturing stations, resulting in reduced registration issues and build time. Abstract: The final functionality of parts produced by Additive Manufacturing (AM) can, in part, be improved by the inclusion of multi-material capabilities. The Multi 3D Manufacturing System uses material extrusion printing (fused deposition modeling technology from Stratasys), solid conductor wire embedding, direct-write, component placement, and micromachining to enable the fabrication of multi-functional products. The material handling methodology, implemented by the Multi 3D System, transports a workpiece between manufacturing stations via a six-axis robot, portable build platform, and a controlled temperature environment or chamber that travels to each manufacturing station. Also discussed in this work, is the investigation and improvement of registration parameters between the two material extrusion printers within this system. The registration was ultimately quantified to have minimal errors: 69 μm along the x-axis, 183 μm along the y-axis, and 215 μm along the z-axis. The fabrication of a multi-colored part demonstrated the automated transfer of the workpiece, which offers early promise for an automated solution for multi-material fabrication using commercially-available fused deposition modeling machines.